Development of a Web-Based Student Attendance Management System Using Visual Basic - Omoniyi, Akintunde Ojo; Oladimeji, Banji Julius; Olojido, Joseph Bamikole (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
Efficient attendance tracking plays a vital role in overseeing and improving student performance in educational settings. Conventional manual attendance methods are typically slow, prone to mistakes, and lack efficiency, resulting in administrative difficulties and possible errors in maintaining accurate records. This study introduces the development and deployment of a web-based Student Attendance Management System built with Visual Basic. The system streamlines the process of recording attendance through automation, enhances data accuracy, and simplifies reporting processes. Key features include user authentication, subject-wise attendance logging, and the generation of detailed reports. The system significantly reduces administrative workload, improves the reliability of attendance data, and facilitates informed decision-making by academic staff. It has been successfully deployed and tested within an academic environment, demonstrating operational efficiency and user satisfaction.